2016
DOI: 10.4062/biomolther.2016.183
|View full text |Cite
|
Sign up to set email alerts
|

3-Deoxysappanchalcone Promotes Proliferation of Human Hair Follicle Dermal Papilla Cells and Hair Growth in C57BL/6 Mice by Modulating WNT/β-Catenin and STAT Signaling

Abstract: 3-Deoxysappanchalcone (3-DSC) has been reported to possess anti-allergic, antiviral, anti-inflammatory and antioxidant activities. In the present study, we investigated the effects of 3-DSC on the proliferation of human hair follicle dermal papilla cells (HDPCs) and mouse hair growth in vivo. A real-time cell analyzer system, luciferase assay, Western blot and real-time polymerase chain reaction (PCR) were employed to measure the biochemical changes occurring in HDPCs in response to 3-DSC treatment. The effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 39 publications
0
20
0
Order By: Relevance
“…Accumulation of β-catenin in the cytosol leads to translocation into the nucleus and activate target genes [27]. While the deletion of Wnt/β-catenin reduced the proliferation of hair follicle progenitor cells and induced the early onset of the catagen phase [28], upregulation of Wnt/β-catenin signaling resulted in a more extensive hair growth [29], especially, Wnt-3α is sufficient to maintain DP cells in the anagen state [24]. In this work, the expression of Wnt-3α and β-catenin protein was increased in OSA and RBM group compared to control group.…”
Section: Resultsmentioning
confidence: 99%
“…Accumulation of β-catenin in the cytosol leads to translocation into the nucleus and activate target genes [27]. While the deletion of Wnt/β-catenin reduced the proliferation of hair follicle progenitor cells and induced the early onset of the catagen phase [28], upregulation of Wnt/β-catenin signaling resulted in a more extensive hair growth [29], especially, Wnt-3α is sufficient to maintain DP cells in the anagen state [24]. In this work, the expression of Wnt-3α and β-catenin protein was increased in OSA and RBM group compared to control group.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, various other compounds have demonstrated stimulatory effect on DPCs at molecular level .…”
Section: Hair Growth Promoting Effectmentioning
confidence: 99%
“…This clinical trial was designed to evaluate the efficacy of a formulated scalp shampoo among volunteers with androgenic alopecia. The formulated scalp shampoo was made by mixing IH extract and CS extract, both of which have been reported to possess hair growth-promoting constituents, such as costunolide and 3-deoxysappanchalcone, respectively [10,11,14]. As compared to the baseline hair count, the statistically significant increase in the hair density and total hair counts after 16 and 24 weeks of using scalp shampoo among the study subjects suggests that the IH and CS extract complex assisted in preventing hair loss and promoting hair growth.…”
Section: Discussionmentioning
confidence: 99%
“…We have recently reported that costunolide, a sesquiterpene lactone present in the roots of Inula helenium L. (Asteraceae), promotes hair growth in vivo, likely by activating intracellular signaling pathways including the Wnt/β-catenin, Shh/Gli, and TGF-β/Smad signaling pathways, which are associated with cell cycle regulation in hair follicular cells [10]. Moreover, 3-deoxysappanchalcone (3-DSC), a sesquiterpene lactone present in Caesalpinia Sappan L. (Leguminosae), has been shown to promote proliferation of dermal papillae and stimulate hair growth partly via activation of Wnt/β-catenin signaling and inhibition of signal transducer and activator of transcription-6 (STAT6)-mediated quiescence of hair follicular cells [11]. However, a clinical trial investigating the effect of extracts of Inula helenium (IH) and Caesalpinia Sappan (CS) on hair growth has not been performed yet.…”
Section: Introductionmentioning
confidence: 99%